2002
DOI: 10.1046/j.1439-0434.2002.00821.x
|View full text |Cite
|
Sign up to set email alerts
|

o‐Hydroxyethylorutin‐Mediated Enhancement of Tomato Resistance to Botrytis cinerea depends on a Burst of Reactive Oxygen Species

Abstract: o‐Hydroxyethylorutin, when applied exogenously to tomato plants was effective in enhancing resistance to Botrytis cinerea infection. Two tomato cultivars, high and low in susceptibility to B. cinerea, were analysed for superoxide anion, hydroxyl radical, hydrogen peroxide generation rates, for changes in lipid peroxidation and activities in superoxide dismutase, peroxidase and catalase. The reactions observed in uninfected tomato plants, in plants infected with B. cinerea, and in those treated with o‐hydroxyet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Nevertheless, the role of ROS in defense against B. cinerea remains controversial. Some studies suggest a positive effect of ROS on plant resistance: Chemical induction of oxidative burst in tomato (Solanum lycopersicon) with O-hydroxyethylorutin resulted in resistance (Malolepsza and Urbanek, 2002) and a biphasic oxidative burst has been reported in bean cells attacked by B. cinerea (Unger et al, 2005). The secondary oxidative burst was much stronger in infections with a nonaggressive rather than with an aggressive strain, which led to the conclusion that ROS-mediated HR-like cell death was able to block B. cinerea.…”
mentioning
confidence: 99%
“…Nevertheless, the role of ROS in defense against B. cinerea remains controversial. Some studies suggest a positive effect of ROS on plant resistance: Chemical induction of oxidative burst in tomato (Solanum lycopersicon) with O-hydroxyethylorutin resulted in resistance (Malolepsza and Urbanek, 2002) and a biphasic oxidative burst has been reported in bean cells attacked by B. cinerea (Unger et al, 2005). The secondary oxidative burst was much stronger in infections with a nonaggressive rather than with an aggressive strain, which led to the conclusion that ROS-mediated HR-like cell death was able to block B. cinerea.…”
mentioning
confidence: 99%
“…In our study, oxalic acid was shown to be ineffective as suppressor on bean leaf discs up to a concentration of 10 m m and the maximum amount found in the infected tissue was 0.5 m m (CH Unger & A. von Tiedemann, unpublished data). On the contrary, Małolepsza and Urbanek (2002) could show that an increase of ROI by o ‐hydroxyethylorutin enhanced the resistance against B. cinerea . This result reversibly confirmed our finding of suppression of ROI enhancing the pathogenicity of the pathogen.…”
Section: Discussionmentioning
confidence: 94%
“…We showed earlier that o-hydroxyethylorutin-a semi-synthetic derivative of rutin, when applied to tomato leaves, limited B. cinerea infection development [31,32]. Higher generation of hydrogen peroxide and superoxide anion at early infection stages in plants pre-treated with o-hydroxyethylorutin and next inoculated with the pathogen seems to be connected with higher resistance of these plants to infection development.…”
Section: Discussionmentioning
confidence: 99%
“…We showed earlier, that o-hydroxyethylorutin treatment of tomato plants limited Botrytis cinerea infection development on them [31,32]. o-Hydroxyethylorutin is semi-synthetic, water soluble, derivative of quercetin-3-rhamnoglucoside (rutin).…”
Section: Introductionmentioning
confidence: 99%